The Road Ahead to Continuous 24-Hour Intraocular Pressure Monitoring in Glaucoma - Kaweh Mansouri (Journal of Ophthalmic & Vision Research, 2014)
Intraocular pressure (IOP) is the only treatable risk factor for glaucoma. Yet, current glaucoma management usually relies on single IOP measurements during clinic hours despite the fact that IOP is a dynamic parameter with individual rhythms. Single IOP measurements underpin all major clinical guidelines on treatment of glaucoma. Other potentially informative parameters, such as IOP fluctuations and peak IOP, have been neglected, and effects of IOP-lowering interventions on such measures are largely unknown. The search for continuous 24-hour IOP monitoring started over 50 years ago, but only recent technological advances have provided clinician-researchers with devices for continuous IOP monitoring. Herein, we discuss innovative approaches with permanent and temporary devices for 24-hour IOP monitoring, such as a contact lens sensor. Despite being in their infancy, these devices may soon enable clinicians to use 24-hour IOP data to improve glaucoma management and reduce the glaucoma-related burden of disease.